(untitled) (Fiep Bulletin - online, 2014)
Urinary incontinence is conceptualized as every condition in which there is involuntary loss of urine, objectively demonstrable, causing social or hygienical problem to the woman. It has multifactorial cause, being a generating element of social exclusion, interfering with the patient’s physical and mental health and impairing his quality of life. The present study was carried out with 10 incontinents women through techniques transvaginal eletroestimulation and specific kinesiotherapy. The results have demonstrated the effectiveness of the conservative treatment, therefore it was possible to observe the improvement of the condition through parameters you quantified, as the test of the strength of the Anus Elevators which had its average increased from 2.2 to 4.2, as well as the reduction of the use of daily protections from 4 to 2, and the reduction of loss episodes in daily activities, as sneezing, coughing, laughing and to lifting weight.